2015
DOI: 10.1155/2015/432910
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism and Sjögren’s Syndrome: A Fortuitous Association or a Shared Immunopathogenesis?

Abstract: Background. The Sjögren Syndrome (SS) can include various manifestations of central nervous system impairment. Extrapyramidal signs are known to be very rare and unusually discovered on early onset in this pathology. Observation. A 46-year-old woman with a history of progressive Parkinsonism for 6 years and a normal brain magnetic resonance imaging was partially improved with levodopa therapy. The later discovery of a sicca syndrome led to performing of further investigations, which revealed the presence of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Several studies have reported that SS was associated with PD, and their results were well correlated with ours [ 17 , 18 ]. Our study involved a total of 143 patients who were suffering from both SS and PD.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Several studies have reported that SS was associated with PD, and their results were well correlated with ours [ 17 , 18 ]. Our study involved a total of 143 patients who were suffering from both SS and PD.…”
Section: Discussionsupporting
confidence: 88%
“…It was mentioned by some studies that autoimmune diseases, for instance rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), psoriasis, osteoarthritis and vasculitis, were well-recognized risk factors of PD because of the neurologic abnormalities caused by immune damage [ 11 16 ]. In addition to these autoimmune factors, few studies introduced that Sjogren’s syndrome (SS) was connected with PD nowadays [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiology Median age at onset was 62.5 years (range, 40 -74 years); 90% were female. Parkinsonism preceded other PSS manifestations in 70% of cases [51,53,54,56,57].…”
Section: Pss-parkinsonismmentioning
confidence: 96%
“…Despite differing methodologies, all found PSS to be associated with increased risk of PD, with adjusted hazard ratios (aHR) ranging from 1.23 to 1.56 [48]. Despite this, reports of parkinsonism in patients with PSS are limitedonly ten met our criteria for analysis [51][52][53][54][55][56][57][58].…”
Section: Pss-parkinsonismmentioning
confidence: 99%